IMPROVING THE STUDENTS’ DESCRIPTIVE TEXT WRITING ABILITY THROUGH THE IMPLEMENTATION OF CLUSTERING TECHNIQUE AT THE TENTH GRADE OF MAN 1 METRO - Wati, Dian Reftya (English Education: Jurnal Tadris Bahasa Inggris, 2018)
The aim of teaching foreign language is defined in terms of four skills, there are listening, speaking, reading, and writing. It clearly shows that the purpose of teaching English is enabling the students to master the four skills. Writing as one of four skill is often ignored, this may be do to a number of factors, such as time consuming of correcting, low motivation, limited time to study writing and lack of teaching technique used. These factors make the English teacher mostly neglect to teach writing. The objective of this research were to know whether clustering technique develops students descriptive text writing ability, teacher’s performance, and students’ participation during teaching learning process at the tenth grade of MAN 1 Metro. To see the teacher’s performance and students’ participation (learning process), the qualitative data was used (questionnaire and observation sheet). Meanwhile, quantitative data (students’ score) was used to know students ability in writing descriptive text (learning product). This research was conducted at MAN 1 Metro. The subject of the research was students of class X.B in academic year 2010/2011. This classroom action research (CAR) was done in three cycles. Each cycle consisted of plan, action, observation, and reflection. The indicators of this research success are if the teacher got minimum 65% from the observation sheet result, 100% students were active during teaching learning process, and 80% students gain score 65 or more. Referring to the research, it can be said that clustering technique can increase students’ descriptive text writing ability, teacher’s performance, and students’ participation during teaching learning process.Keywords: Descriptive Text, Clustering Technique, Writing Ability